Pengaruh Pembiayaan Jual Beli, Pembiayaan Bagi Hasil Dan Intellectual Capital Terhadap Kinerja Keuangan Bank Syariah - Nizar, Achmad Syaiful; Anwar, Mochamad Khoirul (AKRUAL: JURNAL AKUNTANSI, 2015)
AbstractThis research aims to examine the effect of trade financing, profit sharing financing and intellectual capital as measured with islamic Bank-Value Added Intellectual Coeficient (iB-VAIC) towards financial performance as measured with Return On Asset (ROA) of islamic bank. The population in this study is an Islamic commercial bank during the period 2011-2014, of all populations there are 9 Islamic commercial bank that have meet the criteria for the research samples. Data used in this research are annual financial statements published on official website of Islamic commercial bank. The analysis technique used in this research is multiple linear regression analysis. These result shows that trade financing donât affect of financial performance, profit sharing financing donât affect of financial performance and intellectual capital affect of financial performance.